PARENT-CHILD COMMUNICATION IN PREVENTING LGBT BEHAVIORS IN PADANG CITY - Suranta Tarigan, Muhammad Iqbal; Arif, Ernita; Sarmiati, Sarmiati (Jurnal Ranah Komunikasi, 2024)
This research examines the role of parental communication in preventing LGBT behavior in Padang City. The study aims to explore parents' experiences in preventing LGBT behavior through communication, instilling values, and involving fathers in educating children. A qualitative method with a phenomenological approach was employed, conducting in-depth interviews with five research subjects, namely parents who have experience in taking action against LGBT perpetrators, are active in parenting studies, and have experience in raising children to prevent LGBT behavior. The results showed that communication plays a crucial role for parents in, establishing habits such as covering up, educating about body parts that are forbidden to be touched, and encouraging the presence of a father figure both socially and emotionally. Thus, effective communication, instilling values, and father involvement are key factors in preventing the presence of LGBT behavior within the family environment.